Synthesis and In Vitro Antioxidant Evaluation of Some Novel 4, 5-Dihydro-1H, 2, 4-triazol-5-one Derivatives - O. Gursoy Kol; H. Yuksek (E-Journal of Chemistry)
In this study, thirteen novel 4,5-dihydro-1H-1,2,4-triazol-5-one derivatives were synthesized and characterized by elemental analyses and IR, 1H NMR,13C NMR and UV spectral data. The synthesized compounds were analyzed for their in vitro potential antioxidant activities in three different methods. Those antioxidant activities were compared to standard antioxidants such as BHA, BHT and α-tocopherol. The data reveal that the compounds demonstrate a marked capacity for iron binding, especially 5a and 7c In addition to this, the compounds 4 were titrated potentiometrically with TBAH in non-aqueous solvents because of the weak acidic properties of 4,5-dihydro-1H-1,2,4-triazol-5-one ring N-H group.